2007
DOI: 10.1073/pnas.0704186104
|View full text |Cite
|
Sign up to set email alerts
|

Whole-ecosystem study shows rapid fish-mercury response to changes in mercury deposition

Abstract: Methylmercury contamination of fisheries from centuries of industrial atmospheric emissions negatively impacts humans and wildlife worldwide. The response of fish methylmercury concentrations to changes in mercury deposition has been difficult to establish because sediments/soils contain large pools of historical contamination, and many factors in addition to deposition affect fish mercury. To test directly the response of fish contamination to changing mercury deposition, we conducted a whole-ecosystem experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
338
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 408 publications
(361 citation statements)
references
References 33 publications
22
338
1
Order By: Relevance
“…3). The apparent discordance between the Hg profiles appears to support the suggestion that the watershed of LY2 continued to export legacy Hg to the lake during periods of declining atmospheric deposition, a mechanism that has also been observed in modern lake systems (23). The mine was permanently closed in 1975 AD, and currently the only mining of Hg at Huancavelica is artisanal.…”
Section: Resultssupporting
confidence: 50%
“…3). The apparent discordance between the Hg profiles appears to support the suggestion that the watershed of LY2 continued to export legacy Hg to the lake during periods of declining atmospheric deposition, a mechanism that has also been observed in modern lake systems (23). The mine was permanently closed in 1975 AD, and currently the only mining of Hg at Huancavelica is artisanal.…”
Section: Resultssupporting
confidence: 50%
“…[203] In a temperate whole-ecosystem experiment that used additions of stable Hg isotopes to trace the movement of Hg, fish MeHg concentrations responded rapidly to inorganic Hg deposited directly onto the lake surface. [204] On a broad geographic scale, a study of wild fish populations in the United States found that approximately twothirds of the geographic variation in Hg levels of largemouth bass (Micropterus salmoides) was related to the rate of wet atmospheric Hg deposition. [51] Similarly, MeHg bioaccumulation in a fresh water aquatic invertebrate (mosquitoes) was positively correlated with wet atmospheric Hg deposition across a latitudinal gradient in North America that included Alaska.…”
Section: Freshwater Food Websmentioning
confidence: 99%
“…does AMDE Hg take a 'fast track' to biota?). [4,204] In considering the MeHg burden in high trophic level species, it is difficult to estimate which component derives from AMDEs and which derives from the now globally contaminated pool of Hg II cycling in the atmosphere-ocean system. It seems clear that ecosystems in the Arctic Ocean are contaminated with industrial Hg, [255] but it is unclear whether AMDEs contribute significantly to making Arctic ecosystems especially vulnerable to the global Hg cycle.…”
Section: Eastern Beaufort Sea Belugamentioning
confidence: 99%
“…The connection between deposition of inorganic mercury, enhanced during the 1970s, and contamination of ecosystems, due to methylation processes is more complex. Mercury levels in lakes respond rapidly (within years) to changes in mercury deposition directly to their surfaces, but much more slowly (in decades) to changing inputs to their watersheds (6). Although decreases in fish mercury have been reported recently for lakes exposed to reduced mercury deposition (53), other aquatic ecosystems may continue to bio-accumulate Hg due to higher anthropogenic emissions in the 1970s.…”
mentioning
confidence: 99%
“…Harris et al (6) recently reported, however, a whole ecosystem study demonstrating a rapid and direct change in mercury levels in fish resulting from a change in atmospheric mercury. Thus, recent evolution of the atmospheric mercury burden, strongly influenced by anthropogenic emissions, could have played a key role in contamination of many ecosystems.…”
mentioning
confidence: 99%